1996
DOI: 10.1097/00005344-199602000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Nitroprusside on Norepinephrine Overflow and Antidiuresis Induced by Stimulation of Renal Nerves in Anesthetized Dogs

Abstract: To investigate the role of nitric oxide (NO) in the regulation of renal sympathetic nerve activity and renal function, we examined the effect of sodium nitroprusside (SNP), a NO donor, on renal actions induced by renal nerve stimulation (RNS) in anesthetized dogs, with or without blockade of an endogenous NO generation by NG-nitro-L-arginine (NOARG), a NO synthase inhibitor. Low-frequency RNS (0.5-2.0 Hz) enhanced the rate of norepinephrine secretion rate (NESR) from the kidney and decreased urine flow (UF), u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Yamamoto et al 17 found that field stimulation of rat mesenteric arteries caused noradrenaline release, which was decreased by some 50% in the presence of N-nitro-L-arginine (30 mol/L), suggesting NO was necessary for effective neurotransmission. Conversely, Egi et al 18 and Maekawa et al, 19 using the dog, found that intrarenal blockade of NO generation was associated with an increase, whereas NO donors led to a suppression of noradrenaline spillover from the kidney. Despite these diverse reports, there is a view that NO released from the nerve terminals can act presynaptically to exert a tonic inhibitory action on transmitter release.…”
Section: Discussionmentioning
confidence: 94%
“…Yamamoto et al 17 found that field stimulation of rat mesenteric arteries caused noradrenaline release, which was decreased by some 50% in the presence of N-nitro-L-arginine (30 mol/L), suggesting NO was necessary for effective neurotransmission. Conversely, Egi et al 18 and Maekawa et al, 19 using the dog, found that intrarenal blockade of NO generation was associated with an increase, whereas NO donors led to a suppression of noradrenaline spillover from the kidney. Despite these diverse reports, there is a view that NO released from the nerve terminals can act presynaptically to exert a tonic inhibitory action on transmitter release.…”
Section: Discussionmentioning
confidence: 94%
“…However, most evidence suggests that changes in medullary perfusion are due mainly to changes in blood velocity within vasa recta capillaries rather than vasa recta recruitment (see [7] for discussion). A second limitation relates to the fact that NO can affect responses to RNS at pre-junctional sites [20]. Our present experimental approach does not allow us to study separately the impacts of treatments on pre-and post-junctional aspects of sympathetic neuroeffector function.…”
Section: Discussionmentioning
confidence: 98%
“…First, there is evidence that NO can inhibit release of norepinephrine from prejunctional sites in response to RNS (28). Thus enhanced responses of RBF, CLDF, and MLDF to RNS in rabbits pretreated with L-NNA could be due to facilitated release of norepinephrine, to a postjunctional effect to enhance responses to norepinephrine, or to both.…”
Section: Discussionmentioning
confidence: 99%